2022
DOI: 10.1039/d1ta10669d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ion transport behaviors in composite polymer electrolyte: the case of a looser chain folding structure

Abstract: All-solid-state batteries based on composite polymer electrolytes (CPEs) have drawn significant attention due to their high energy density, security and flexibility. Usually, the improvement of electrochemical performance of CPEs is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The lower ionic conductivity of CPEs with 500 nm particles after cyclic compression thus reveals a potential negative impact on the interfacial lithium-ion conduction pathways caused by mechanical cycling. Nuclear magnetic resonance (NMR) methods have shown that smaller particles (30 vs 200 nm) are associated with looser chain folding structure based on characteristic relaxation times of polycaprolactone (PCL) electrolytes with LiTFSI and Al 2 O 3 particles . Alteration of chain folding over many cycles of structural deformation can have an adverse effect on lithium-ion transport through the electrolyte in a way that is more pronounced for composites with smaller particles.…”
Section: Resultsmentioning
confidence: 99%
“…The lower ionic conductivity of CPEs with 500 nm particles after cyclic compression thus reveals a potential negative impact on the interfacial lithium-ion conduction pathways caused by mechanical cycling. Nuclear magnetic resonance (NMR) methods have shown that smaller particles (30 vs 200 nm) are associated with looser chain folding structure based on characteristic relaxation times of polycaprolactone (PCL) electrolytes with LiTFSI and Al 2 O 3 particles . Alteration of chain folding over many cycles of structural deformation can have an adverse effect on lithium-ion transport through the electrolyte in a way that is more pronounced for composites with smaller particles.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the presence of nanoparticles in each phase of the polymer blend can lead to a restriction effect on the molecular chain motions and thus a change in its dynamic transitions. [39][40][41] On the other hand, the dynamics of the chain can be evaluated by changes in the F I G U R E 3 (A) Storage modulus and (B) complex viscosity versus angular frequency and (C) Cole-Cole plot at 190 C for PP8/EC2 and nanocomposite samples prepared by different feeding methods containing 2 phr multiwalled carbon nanotubes damping factor (tan δ; peak area) and the glass transition temperature (T g ) in the DMTA curves. [24,42,43] In this regard, a reduction in the damping factor and also a shift of the T g to higher temperature reveal a slowing down of the molecular chain motions.…”
Section: Selective Localization Of Mwcnts Based On Kinetic Parametersmentioning
confidence: 99%
“…However, the anionic dynamics generally supersedes the cationic dynamics, resulting in low t Li+ in PEO systems, since the anion mobility is less restricted by the polymer segmental motions . Being a semicrystalline polyester with a glass-transition temperature of −65 °C and a melting temperature around 55 °C, poly­(ε-caprolactone) (PCL) was selected as a matrix candidate since it displays in fact notably similar physical properties as PEO. Especially, the PCL exhibits a strong Li-ion solvating capability, which is expected to promote the Li-ion transport. Zhang et al reported a PCL-based CPE with a high degree of LiTFSI dissociation reaching up to 45 wt % .…”
Section: Introductionmentioning
confidence: 99%